Assessing patient‐centred communication in teaching: a systematic review of instruments. Issue 11 (1st August 2017) - Brouwers, Marianne; Rasenberg, Ellemieke; van Weel, Chris; Laan, Roland; van Weel‐Baumgarten, Evelyn
Abstract : Context: Patient‐centred communication is a key component of patient centredness in medical care. Therefore, adequate education in and assessment of patient‐centred communication skills are necessary. In general, feedback on communication skills is most effective when it is provided directly and is systematic. This calls for adequate measurement instruments. Objectives: The aim of this study was to provide a systematic review of existing instruments that measure patient centredness in doctor–patient communication and can be used to provide direct feedback. Methods: A systematic review was conducted using an extensive validated search strategy for measurement instruments in PubMed, EMBASE, PsycINFO and CINAHL. The databases were searched from their inception to 1 July 2016. Articles describing the development or evaluation of the measurement properties of instruments that measure patient centredness (by applying three or more of the six dimensions of a published definition of patient centredness) in doctor–patient communication and that can be used for the provision of direct feedback were included. The methodological quality of measurement properties was evaluated using the COSMIN checklist. Results: Thirteen articles describing 14 instruments measuring patient centredness in doctor–patient communication were identified. These studies cover a wide range of settings and patient populations, and vary in the dimensions of patient centredness applied and in methodological quality on aspects of reliability and validity. Conclusions: This review gives a comprehensive overview of all instruments available for the measurement of patient centredness in doctor–patient communication that can be used for the provision of direct feedback and are described in the literature. Despite the widely felt need for valid and reliable instruments for the measurement of patient‐centred communication, most of the instruments currently available have not been thoroughly investigated. Therefore, we recommend further research into and enhancement of existing instruments in terms of validity and reliability, along with enhancement of their generalisability, responsiveness and aspects of interpretability in different contexts (real patients, simulated patients, doctors in different specialties, etc.). Comprehensibility and feasibility should also be taken into account.